The woman question in Plato's Republic - Townsend, Mary (Lexington Books, 2017)
In this book, Mary Townsend proposes that, contrary to the current scholarship on Plato's Republic, Socrates does not in fact set out to prove the weakness of women. Rather, she argues that close attention to the drama of the Republic reveals that Plato dramatizes the reluctance of men to allow women into the public sphere and offers a deeply aporetic vision of women's nature and political position--a vision full of concern not only for the human community, but for the desires of women themselves. --! From back cover.